Living Speech : Resisting the Empire of Force - White, James Boyd, 1938- (Book collections on Project MUSE., 2006)
Language is our key to imagining the world, others, and ourselves. Yet sometimes our ways of talking dehumanize others and trivialize human experience. In war other people are imagined as enemies to be killed. The language of race objectifies those it touches, and propaganda disables democracy. Advertising reduces us to consumers, and cliches destroy the life of the imagination. How are we to assert our humanity and that of others against the forces in the culture and in our own minds that would deny it? What kind of speech should the First Amendment protect? How should judges and justices t.